2016
DOI: 10.7759/cureus.465
|View full text |Cite
|
Sign up to set email alerts
|

Baastrup’s Disease: An Often Missed Etiology for Back Pain

Abstract: Baastrup’s disease is a relatively common disorder of the vertebral column, characterized by low back pain arising from the close approximation of adjacent posterior spinous processes and resultant degenerative changes, most commonly at L4-L5. Though fairly common, Baastrup’s disease is overwhelmingly underdiagnosed and often missed due to a lack of knowledge and/or improper diagnostic techniques, leading to frequent mistreatment. We present a case of a 56-year-old man who presented with chronic, ongoing low b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
1
14
0
2
Order By: Relevance
“…Treatment of Baastrup’s syndrome is an ongoing topic of debate; both conservative and surgical options are available for treatment. It may improve with localized interspinous injection of anesthetic and there are conflicting reports of improvement with partial excision of spinous process [8].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of Baastrup’s syndrome is an ongoing topic of debate; both conservative and surgical options are available for treatment. It may improve with localized interspinous injection of anesthetic and there are conflicting reports of improvement with partial excision of spinous process [8].…”
Section: Discussionmentioning
confidence: 99%
“…Although little known, BD is often a source of low back pain. [ 7 8 9 10 ] This underestimation can derive from the fact that it is often accompanied with other degenerative lumbar spine disease. Modern imaging techniques have enabled us to know the peculiarities of this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded Baastrup's disease was part of the expected spinal degenerative changes with age and urged caution before diagnosing Baastrup's disease as the sole cause of back pain. A study with the use of interspinous distraction and stabilizing devices clearly demonstrated that stabilizing the interspinous space leads to cyst resolution and symptomatic relief, suggesting that cystic degenerative changes are a reaction to the instability resulting from deterioration and laxity of the degenerative interspinous ligament [ 14 - 15 ] (Figure 3 ).…”
Section: Reviewmentioning
confidence: 99%
“…If the predominant symptoms are related to neurogenic claudication or radiculopathy, then surgical decompression or stabilization may be necessary [ 16 ]. In the evaluation of clinical symptoms relative to radiologic findings on CT and MRI, it is critical to not over diagnose the underlying degenerative findings [ 15 ]. If the patient has only localized postural back pain with extension without any radicular findings or claudication, then initial use of simple interspinous infiltration or radiofrequency ablation within the interspinous ligament should be the appropriate initial treatment after failing conservative measures.…”
Section: Reviewmentioning
confidence: 99%